2015
DOI: 10.1002/app.42617
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive hollow magnetic microspheres with hyperthermia and controlled release properties

Abstract: Thermoresponsive hollow magnetic microspheres consisting of a hollow magnetic core, a carbon shell, and a smart polymer layer are presented in this article. A carbon nanomaterial was used as a steric stabilizer for Fe 3 O 4 nanoparticles and a supporter for polymer. The thermoresponsive monomer, N-isopropyl acrylamide, was grafted on the carbon-encapsulate hollows by surface radical polymerization. The experimental results indicate that the composites had a phase-transition temperature around 438C and a satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…It was noticeable that the particle size was ~170 nm by TEM, smaller than the average size determined by DLS (205.4 ± 3.44 nm) at 25 °C. This was because DLS showed HSA nanoparticles in the hydrated state, while TEM displayed particle size in the dried state [28,29]. A favorable stability of TP 5 -NPs was ensured in the study of stability for 72 h in vitro, which can prolong retention of TP 5 -NPs in tumor tissue [30].…”
Section: Discussionmentioning
confidence: 99%
“…It was noticeable that the particle size was ~170 nm by TEM, smaller than the average size determined by DLS (205.4 ± 3.44 nm) at 25 °C. This was because DLS showed HSA nanoparticles in the hydrated state, while TEM displayed particle size in the dried state [28,29]. A favorable stability of TP 5 -NPs was ensured in the study of stability for 72 h in vitro, which can prolong retention of TP 5 -NPs in tumor tissue [30].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure (d), EDS demonstrated that Fe 3 O 4 contained more Fe and less C. The Fe signal consisted of the characteristic peaks of the magnetite nanoparticles, and the less intense C signal might originate from the carbon‐coated copper grid . The N signal as shown in Figure (e,f) was assigned to the graft monomer (AM), which proved that the polymer shell was successfully coated on the surface of the Fe 3 O 4 nanoparticles . In addition, the results showed that the amount of N increased with increasing monomer dose, which further indicated that controllable core/shell structures could be successfully generated.…”
Section: Resultsmentioning
confidence: 97%
“…Other applications such as microrheology applications [34,157], lab-on-a-chip systems [158], drug delivery [98,159], hyperthermia [160,161] and microfluidics/mixing by applying a sinusoidal #» B of 30 mT and a frequency of 20 Hz, obtaining a mixing efficiency of ≈ 80% and an increment in efficiency to 95% by reducing the frequency to 5 Hz [150].…”
Section: Magnetic Bead Composites For Torque Generation At the Micron Scalementioning
confidence: 99%